Distribution and determinants of patient satisfaction in oncology: A review of the literature - Christopher G Lis; Mark Rodeghier; Digant Gupta (Patient Preference and Adherence, 2009)
Christopher G Lis, Mark Rodeghier, Digant GuptaCancer Treatment Centers of America® at Midwestern Regional Medical Center, 2610 Sheridan Road, Zion, IL, 60099, USAAbstract: Cancer is one of the leading causes of morbidity and mortality in the United States. It places considerable mental, physical, and emotional stress on patients and requires them to make major adjustments in many key areas of their lives. As a consequence, the demands on health care providers to satisfy the complex care needs of cancer patients increase manifold. Of late, patient satisfaction has been recognized as one of the key indicators of health care quality and is now being used by health care institutions for monitoring health care improvement programs, gaining accreditation, and marketing strategies. The patient satisfaction information is also being used to compare and benchmark hospitals, identify best-performance institutions, and discover areas in need of improvement. However, the existing literature on patient satisfaction with the quality of cancer care they receive is inconsistent and heterogeneous because of differences in study designs, questionnaires, study populations, and sample sizes. The aim of this review was therefore to systematically evaluate the available information on the distribution and determinants of patient satisfaction in oncology.Keywords: patient satisfaction, determinants, oncology